Organic geochemistry, sedimentary environment, and organic matter enrichment of limestone-marlstone rhythms in the middle Permian northern Sichuan Basin, China. (December 2021) - Qian, Pang; Guang, Hu; Xihua, Zhang; Cong, Chen; Zhaolong, Gao; Shujiao, Shan; Yangui, Chen; Chaowei, Hu; Jie, You
Abstract: Limestone-marlstone (LM-MR) rhythms widely develop in the middle Permian Maokou Formation of Sichuan basin, and they are regarded as potential source rocks and important shale gas targets due to their high organic matter contents. In this study, LM-MR rhythms in the lower part of the Maokou Formation in the Changjianggou section of the Sichuan basin are selected for research because of their moderate thermal maturity of organic matter. A series of studies are implemented to investigate the organic geochemical characteristics, formation processes, organic matter enrichment mechanism, and hydrocarbon potentials of these LM-MR rhythms, from perspectives of sedimentology, organic petrology, and geochemistry. Organic matter in marlstones is suggested to be mainly contributed by cyanobacteria according to organic petrographic results, low regular steranes/17α-hopanes, and high mid-chain branched monomethyl alkanes (MMAs). In contrast, organic matter in limestones is suggested to mainly result from benthic algae. Marlstone samples have more negative carbon and oxygen isotopes and higher Fe/Mn ratios than the limestone samples, suggesting sedimentary environments with shallower water depth and stronger restrictions during marlstone deposition. Moreover, marlstone samples have lower ratios of gammacerane/C30 αβ hopane than limestone samples, suggesting lower water salinity during marlstone deposition. Furthermore, marlstone samples have higher TOC contents than limestone samples, and this is attributed to the less carbonate dilution, the suboxic-anoxic environment, and the increased productivity during marlstone deposition, all of which are initially controlled by the high-frequency relative sea-level change. The hydrocarbon potential analysis suggests that LM-MR rhythms in the study area are with high TOC contents, Type II organic matter, and moderate thermal maturity. Highlights: Marlstone and limestone are mainly contributed by cyanobacteria and benthic algae respectively. Marlstones are deposited in more restricted environments with shallower water than limestones. High paleoproductivity and suboxic-anoxic condition result in high TOC of marlstones. Maokou Formation LM-MR rhythms are potential good source rocks.